Author Correction: Norgestimate inhibits staphylococcal biofilm formation and resensitizes methicillin-resistant Staphylococcus aureus to β-lactam antibiotics. (December 2017) - Yoshii, Yutaka; Okuda, Ken-ichi; Yamada, Satomi; Nagakura, Mari; Sugimoto, Shinya; Nagano, Tetsuo; Okabe, Takayoshi; Kojima, Hirotatsu; Iwamoto, Takeo; Kuwano, Kazuyoshi; Mizunoe, Yoshimitsu
A correction to this article has been published and is linked from the HTML version of this article.